A study on prevalence of gestational diabetes mellitus and its associated risk indicators in pregnant women attending antenatal clinic in a tertiary health centre - N., Vinoth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Gestational diabetes mellitus (GDM) is defined as impaired glucose tolerance (IGT) with onset or first recognition during pregnancy it is associated with adverse maternal and perinatal outcome. The prevalence of gestational diabetes mellitus (GDM) has been increasing globally, with urbanization, sedentary lifestyle, physical inactivity and dietary changes as significant contributing factors. Hence this study was done to study the prevalence of GDM and its associated risk indicators. Methods: This was a cross sectional study. During the study period, 164 antenatal women between on her first visit were screened for GDM using 50 gm glucose challenge test in all patients if normal it was repeated between 24- 28 weeks of pregnancy and then at 32 weeks. If abnormal 75 gm oral glucose tolerance test (OGTT) done and also repeated at 24-28 weeks of gestation and diagnosed to have GDM. Risk factors for GDM were noted. Results: The prevalence of GDM in the study population was 23.78%. Prevalence of GDM cases was significantly associated with increased body mass index (BMI). BMI>25 kg/m2 (0.001%) has strong association. Family history of diabetes, previous macrosomia/large for gestational age (LGA) baby and past history of GDM (p<0.00001) also has strong association. Maternal age >25 years (0.001) significantly associated with increased prevalence of GDM but parity was not statistically associated (p=0.358). Incidence of pre-eclampsia and polyhydramnios were significantly higher among GDM cases. Conclusions: The prevalence of gestational diabetes mellitus (GDM) has been increasing globally, with urbanization, sedentary lifestyle, physical inactivity and dietary changes as significant contributing factors. Maternal age >25 years, BMI>25 kg/m2, family history of diabetes, past GDM and previous LGA baby were important risk factors for GDM. Most of the adverse outcome are preventable by early detection and proper glucose control. Therefore, we recommend screening pregnant women for GDM and establishment of separate diabetic antenatal clinic with availability of diabetician and diabetic councillor.